The influence of pyrophosphate, condensed phosphates, phosphonates and other phosphate compounds on the dissolution of hydroxyapatite in vitro and on bone resorption induced by parathyroid hormone in tissue culture and in thyroparathyroidectomised rats - Russell, R; Mühlbauer, R; Bisaz, S; Williams, D; Fleisch, H (Springer-Verlag, 1970)
Earlier studies have shown that inorganic pyrophosphate (PP i) inhibits the dissolution of hydroxyapatite crystals in vitro and it has been suggested that PP i might be a physiological regulator of bone resorption. In this study PP 1 and other phosphate compounds have been tested for their ability to inhibit bone resorption induced by parathyroid hormone in mouse calvaria and to inhibit the rise in plasma calcium induced by parathyroid hormone in thyroparathyroidectomised rats on a low calcium diet. Orthophosphate, pyrophosphate, polyphosphate and two polymeric phosphate inhibitors of phosphatases did not inhibit the resorption of calvaria or the rise in plasma calcium. In contrast, several phosphonates containing P-C-P bonds retarded the dissolution of hydroxyapatite crystals in vitro, and, at concentrations down to 1.6×10 -6M, inhibited bone resorption in tissue culture. Some diphosphonates also inhibited the rise in plasma calcium in thyroparathyroidectomised rats. One reason for the difference between the effects of compounds containing P-O-P and P-C-P bonds may be related to the greater resistance of the latter to chemical and enzymic hydrolysis. Phosphonates may provide a model for the effect of endogenous PP 1 in bone, and might be of use in elucidating provide a model for the effect of endogenous PP 1 in bone, and might be of use in elucidating mechanisms of bone formation and resorption and in the therapy of diseases that involve increased resorption of bone. © 1970 Springer-Verlag.